Juvenile Violent Victimization and Adult Criminal Outcomes: The Role of Military Service as a Turning Point in Young Adulthood - Orak, Ugur (Journal of interpersonal violence, 2024)
Previous research has consistently shown that juvenile violent victimization is associated with an increased risk of future criminal involvement, a phenomenon commonly known as victim-offender overlap. Despite a growing interest in the factors underlying this overlap, potential roles of major life transitions and turning points that may interrupt and reshape the nature of this developmental association have garnered less academic attention. Analyzing nationally representative data from waves I, IV, and V of the National Longitudinal Study of Adolescent to Adult Health (Add Health; n = 10,205), this study investigates the association between juvenile violent victimization and adult criminal outcomes (i.e., violent offending, non-violent offending, arrest, and incarceration) and whether this association is moderated by military service with and without combat experience in young adulthood. Employing a series of logistic regression analyses and adjusting for a host of covariates, measures of selection, and criminogenic traits, we found that juvenile violent victimization was significantly associated with greater odds of violent offending, arrest, and incarceration in adulthood. Among individuals with violent victimization histories, military service with no combat experience was associated with a 16% decrease in the odds of incarceration in adulthood. Combat experience, however, was associated with over seven times greater odds of violent offending in adulthood for these individuals. These findings have important implications for theory, research, and practice, and highlight the relevance of life transitions and turning points in general, and military service in particular, in mitigating or perpetuating the criminogenic impacts of violent victimization in the life course.